2017
DOI: 10.1111/medu.13380
|View full text |Cite
|
Sign up to set email alerts
|

‘Playing the game’: How do surgical trainees seek feedback using workplace-based assessment?

Abstract: Trainees' perceptions of the purpose of WBA and their relationship with their trainer informed when they chose to seek feedback. Trainees who perceived WBA as a test were led to 'play the game' by seeking positive and avoiding negative feedback. Outside of WBA, trainees sought negative feedback, which was most important for change in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
117
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(118 citation statements)
references
References 37 publications
0
117
0
1
Order By: Relevance
“…They reported that the assessment messages they received were fair and useful, and promoted deeper understanding and learning . One trainee commented:
…if it is done well you can get an awful lot of learning opportunities out of it and …it gives you an awful lot of feedback.
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…They reported that the assessment messages they received were fair and useful, and promoted deeper understanding and learning . One trainee commented:
…if it is done well you can get an awful lot of learning opportunities out of it and …it gives you an awful lot of feedback.
…”
Section: Resultsmentioning
confidence: 99%
“……if it is done well you can get an awful lot of learning opportunities out of it and …it gives you an awful lot of feedback.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations